Oral Squamous Cell Carcinoma in Atrophic–Erosive Lichen Planus: 10-Year Rehabilitative Case Report - Eduardo Anitua; Laura Piñas; Mohammad H. Alkhraisat (Case Reports in Dentistry)
Patients with oral lichen planus can sometimes develop malignancy of the process and develop oral squamous cell carcinoma or another type of cancer. Close monitoring of the lesions and early diagnosis is important to increase patient survival. Once cancer treatment has been performed, the therapeutic options for restoring masticatory and phonatory function, in addition to resolving the aesthetic sequelae, are important. In the present clinical case, we show a patient who was treated and followed over a long period of time for both her carcinoma and her subsequent rehabilitation with implants.